Behavioural bias in investment decisions: moderate role of self-control - Muhadjir Anwar; Sulastri Irbayuni; Ira Wikartika; Heri Pratikto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Behavioural aspects in making financial or investment decisions have been inspired by the increasing role of behaviour as determinants of buying and selling securities. This study aims to analyze the effect of loss aversion and mental accounting on investment decisions and the role of self-control as a moderating variable on the effect of loss aversion and mental accounting on investment decisions. The research sample was 137 Small and Medium Footwear Industries in Mojokerto City. The sampling technique was probability sampling. Thus, this research used simple random sampling. The respondents of this research were the owners or managers of Small and Medium Industries (SMIs). The primary data was obtained directly from respondents’ answers to questionnaire statements. The data analysis method was Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that: First, loss aversion and mental accounting have a significant positive effect on investment decisions. Second, self-control is not moderate the effect of loss aversion on investment decisions but moderates the effect of mental accounting on investment decisions. Psychomotor aspects of mental accounting from owners or managers of SMIs is realizing that the existing accounts receivable is the primary source of income for the business.